The euro system and the federal reserve system compared: Facts and challenges - Karlheinz Ruckriegel; Franz Seitz (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
This paper compares the Federal Reserve System and the Eurosystem in four aspects. These are the institutional level, the monetary policy instruments, the operational framework and the monetary policy strategy applied. It highlights the similarities and the differences as well as the efficiency of the different settings.
Keywords: E42; E52; 330